Reorienting Islamic Education: Southeast Asia Comparative Study of Maqāṣid al-Sharī‘ah and Artificial Intelligence - Muh. Rezky Zulkarnain; Muhammad Fikri; Abd. Rahman; Sardil Mutaallif; Winanda Fajri Al Hakim; Eka Merdekawati Djafar; Haura Mudya Maysha; Wiranti (Multicultural Islamic Education Review, 2026)
Islamic education, particularly in Islamic boarding schools, faces serious challenges amid globalization, digitalization, and the development of artificial intelligence (AI), which require a reorientation of the educational paradigm in order to remain relevant, adaptive, and equitable. This article analyzes the application of the principles of Maqāṣid al-Sharī‘ah in the Islamic education system and examines the potential and challenges of integrating AI into Islamic boarding school education from a maqāṣidī perspective. This study uses a qualitative method with a socio-legal approach through literature review and documentation of Islamic legal sources, academic literature, education policies, and empirical studies in Indonesia and Malaysia. The results show that Islamic boarding schools have basically implemented maqāṣid, especially in the aspects of ḥifẓ al-dīn and character building, but it is still symbolic and traditional, not yet touching on substantive dimensions such as the development of critical thinking (ḥifẓ al-‘aql), mental health (ḥifẓ al-nafs), economic empowerment (ḥifẓ al-māl), professional readiness, and gender equality (ḥifẓ al-nasl). The integration of AI has the potential to strengthen santri learning, governance, and digital literacy, but it also risks weakening critical thinking, reducing scientific authority, widening social gaps, and creating value bias if not guided ethically. Comparatively, Indonesia and Malaysia have not yet implemented AI and maqāṣid systematically. Therefore, an integrative and ethical Maqāṣid al-Sharī‘ah-based Islamic education model is needed so that AI functions as a means of benefit, not a source of new harm.